Relationship of Periodontitis in Pregnancy to Premature and Low Birth Weight in a Libyan Women Sample - ELdegheli, Nuzha; Mahfoud, Salma; Busarira, Musa; Ingafou, Mohamed (Libyan Journal of Dentistry, 2019)
To assess the relation between periodontitis and the risk of preterm delivery/low birth weight among Libyan women in Benghazi. Methods: A total of 300 Libyan pregnant women attended to the reception of labour department of Al- Jomhuriya Hospital in Benghazi for delivery from May to August 2010 were included in this study. After recording and exclusion of traditional risk factors for premature/low birth weight like; age, weight, smoking, prenatal care, medical history, gestational and obstetric history. They were examined for periodontal status using Plaque Index, Gingival Index and Periodontal Disease Index, all the data obtained were analyzed with the day of delivery and birth‘s weight. Results: The periodontal disease index score (PDI) showed that 47% of the sample had moderate gingivitis, 29% of the sample had mild gingivitis, 10% had severe gingivitis while 11% had mild periodontitis. According to gingival index score, moderate gingivitis had high percentage (60%) which is related to high percentage (51%) in plaque index score. PDI showed insignificant relationship with PLBW at P-value = 0.849. Conclusion: This study suggests that there is no association between periodontitis and premature/low birth weight among Libyan ladies in Benghazi.